Effects of Tillage Systems on Physical Status and Organic Matter Turnover of the Soil - Huzsvai, László; Rátonyi, Tamás; Nagy, János; Megyes, Attila (Acta Agraria Debreceniensis, 2003)
The cultivation technology for those plant, that play a key role in arable land production need to be renewed in order to reduce production costs and to protect arable land. The modernisation of technologies can only be achieved by applying appropriate tillage systems. Our measurements were carried out on chernozem soil with lime deposits at the Látókép Experimental Station of the Center for Agricultural Sciences, Debrecen University, in long term tillage experiments set up in 1989. We examined the typical physical parameters, the albedo, field capacity, the bulk density of the soil, organic carbon content (humus %) and the measured pH-values in the water solution within the two tillage variations. We have also modelled nitrogen cycle formation in different treatments. A significant difference occured between the albedos of the two soils, which may be the result of significant amounts of stem remaining on the surface in the case of the reduced tillage method. The yellow, waxy stem of maize reflects 21% of the sun’s rays, especially at the beginning of the vegetation period, when its decomposition has only just started. This delys the warming up in early spring, which delays the sowing time of maize and reduces evaporation. In the two tillage variations, the water management characteristics do not differ practically, the wilting point field capacity are in accordance. In reduced tillage methods, the so-called „plough-pan” can be well measured at 15-20 cm, while in winter ploughing it is at 30 cm. The humus % of the soil does not differ in the two tillage variations, but due to the difference in bulk density this means a different humus and organic nitrogen content. The organic nitrogen content is greater in the reduced tillage method. On the basis of pH value evaluations, we could not detect significant differences in the two tillage variations. The organic nitrogen content of areas where reduced tillage method was applied is higher than in areas where conventional winter ploughing was applied.